Critical Steps of Plasmodium falciparum Ookinete Maturation - Siciliano, Giulia; Costa, Giulia; Suárez-Cortés, Pablo; Valleriani, Angelo; Alano, Pietro; Levashina, Elena A. (Frontiers in Microbiology, 2020)
The egress and fertilization of Plasmodium gametes and development of a motile ookinete are the first crucial steps that mediate the successful transmission of the malaria parasites from humans to the Anopheles vector. However, limited information exists about the cell biology and regulation of this process. Technical impediments in the establishment of in vitro conditions for ookinete maturation in P. falciparum and other human malaria parasites further constrain a detailed characterization of ookinete maturation. Here using fluorescence microscopy and immunolabelling, we compared P. falciparum ookinete maturation in A. coluzzii mosquitoes in vivo and in cell culture in vitro. Our results identified two critical steps in ookinete maturation that are regulated by distinct mosquito factors, thereby highlighting the role of mosquito environment in transmission efficiency of malaria parasites.